2016
DOI: 10.1038/srep32742
|View full text |Cite
|
Sign up to set email alerts
|

Giant strain control of magnetoelectric effect in Ta|Fe|MgO

Abstract: The exploration of electric field controlled magnetism has come under scrutiny for its intriguing magnetoelectric phenomenon as well as technological advances in spintronics. Herein, the tremendous effect of an epitaxial strain on voltage-controlled perpendicular magnetic anisotropy (VPMA) is demonstrated in a transition-metal|ferromagnet|MgO (TM|FM|MgO) heterostructure from firstprinciples electronic structure computation. By tuning the epitaxial strain in Ta|Fe|MgO as a model system of TM|FM|MgO, we find dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
5
8
0
Order By: Relevance
“…In the present study, the VCMA can be determined by the curve slope of the electric-field or n e dependence of MAE. The nonlinear parabola-like shape behavior of the VCMA within a small range of n e (−1 < n e < +1) is quite typical in most magnetoelectric materials, as reported in previous calculations [50][51][52] and experiments [53][54][55].…”
Section: Resultssupporting
confidence: 78%
“…In the present study, the VCMA can be determined by the curve slope of the electric-field or n e dependence of MAE. The nonlinear parabola-like shape behavior of the VCMA within a small range of n e (−1 < n e < +1) is quite typical in most magnetoelectric materials, as reported in previous calculations [50][51][52] and experiments [53][54][55].…”
Section: Resultssupporting
confidence: 78%
“…This implies that the AFM-FM transition at the interface accompanies the strong out-of-plane orbital ( and ) hybridization between the Ta 5 d and Fe 3 d states. A similar argument applies to the FeRh/MgO interface, as addressed in previous ab initio calculations 5 , 22 .
Figure 3 Spin and d -orbital decomposed PDOS of ( a ) Fe(I V ) in FeRh/MgO and ( b ) Fe(I Ta ) and ( c ) Ta(I) in Ta/FeRh/MgO multilayers.
…”
Section: Resultssupporting
confidence: 60%
“…The other spin-antiparallel configurations, i.e., Type-I (or A-AFM) and Type-III (or C-AFM), have been excluded because they were found to have relatively high energies than those for the AFM-II and FM phases 21 . The preferred adsorption sites of Fe atoms were atop O at the FeRh/MgO interface and a hollow site at the Ta/FeRh interface, which are analogues to a Ta/Fe/MgO multilayer 22 . An experimental lattice constant (4.212 Å) for MgO was adopted for the in-plane lattice of supercells, which was matched to the optimized bulk lattices of AFM-II and FM FeRh within 0.5 and 1.1%, respectively 5 .…”
Section: Resultsmentioning
confidence: 98%
“…Recently, strain-induced modulation of electronic structures and its influence on the VCMA effect has attracted attention [130,131]. For example, Hibino et al reported a high VCMA coefficient of +1600 fJ/Vm in a Pt/Co/Pd/MgO structure at 10 K [95].…”
Section: Physical Origin Of the Vcma Effectmentioning
confidence: 99%